Characterization of Wideband Semiconductor Optical Amplifiers based on OptiSystem and MATLAB - YUAN SUAN, ONG; Kharraz, O. M.; SULAIMAN, A. H.; ABDULLAH, F.; MD YUSOFF, NELIDYA (International Journal of Integrated Engineering, 2018)
A study about different types of semiconductor optical amplifiers (SOA)s - linear, nonlinear and in-line SOAs modelling is carried out. The SOA key performance characteristics covered in this paper include optical gain, power, and amplified spontaneous emission (ASE) noise figure. These characteristics definition are included in this work together with the tabulation of each SOA specification parameter operating in the operational conventional (C-) band. The first modelling of SOA wideband travelling wave (TW) component is done through a simple configuration using OptiSystem software. Next, the second modelling method is simulated through numerical steady-state model using MATLAB software. Each graphical result is explained and discussed according to the operational characteristic theories of SOA along with the evaluation for the best performance among the types of SOAs. The contrasted result among them had shown that linear SOA has the most ideal and competitive characteristics, as compared to the nonlinear and in-line SOAs, especially a better choice as gain medium in the multiwavelength fiber laser (MWFL) application.